Phase III double-blind study comparing the efficacy and safety of proposed biosimilar MYL-1402O and reference bevacizumab in stage IV non-small-cell lung cancer. (November 2021) - Socinski, Mark A.; Waller, Cornelius F.; Idris, Tazeen; Bondarenko, Igor; Luft, Alexander; Beckmann, Katrin; Vishweswaramurthy, Ashwini; Loganathan, Subramanian; Donnelly, Charles; Hummel, Matthew A.; Shapiro, Roxann; Woods, Melody; et al.
Purpose: This phase III study compared the efficacy and safety of proposed biosimilar MYL-1402O with reference bevacizumab (BEV), as first-line treatment for patients with stage IV non-squamous non-small-cell lung cancer. Patients and methods: Patients were randomly assigned (1:1) to receive MYL-1402O or bevacizumab with carboplatin-paclitaxel up to 18 weeks (6 cycles), followed by up to 24 weeks (8 cycles) of bevacizumab monotherapy. The primary objective was comparison of overall response rate (ORR), based on independently reviewed best tumor responses as assessed during the first 18 weeks. ORR was analyzed per US Food and Drug Administration (ratio of ORR) and European Medicines Agency (difference in ORRs) requirements for equivalence evaluation. Secondary end points included progression-free survival, disease control rate, duration of response, overall survival, safety, and immunogenicity over a period of 42 weeks, and pharmacokinetics (up to 18 weeks). Results: A total of 671 patients were included in the intent-to-treat population. The ratio of ORR was 0.96 [confidence interval (CI) 0.83, 1.12] and the difference in ORR was −1.6 (CI −9.0, 5.9) between treatment arms; CIs were within the predefined equivalence margins. Overall, the incidence of treatment-emergent adverse events and serious adverse events was comparable. Treatment-emergent anti-drug antibody (ADA) positivity was transient, with no notable differences between treatment arms (6.5% versus 4.8% ADA positivity rate in MYL-1402O versus BEV, respectively). The incidence of neutralizing antibody post-baseline was lower in the MYL-1402O arm (0.6%) compared to the bevacizumab arm (2.5%). Conclusions: MYL-1402O is therapeutically equivalent to bevacizumab, based on the ORR analyses, with comparable secondary endpoints. Trial Registry Information: EU Clinical Trials Register, Registration # EudraCT no. 2015-005141-32https://www.clinicaltrialsregister.eu/ctr-search/search?query=2015-005141-32 Plain language summary: Previous studies established bioequivalence of the proposed bevacizumab biosimilar MYL-1402O to reference bevacizumab. In this randomized, double-blind, phase III trial, MYL-1402O ( n = 337) demonstrated comparable efficacy to bevacizumab ( n = 334) in treating advanced non-squamous non-small-cell lung cancer per Food and Drug Administration and European Medicines Agency requirements for equivalence; the ratio of objective response rate (ORR) was 0.96 [90% confidence interval (CI) 0.83, 1.12] and the difference in ORR (MYL-1402O:bevacizumab) was −1.6 (95% CI −9.0, 5.9). Median progression-free survival at 42 weeks was comparable: 7.6 (7.0, 9.5) with MYL-1402O versus 9.0 (7.2, 9.7) months ( p = 0.0906) with bevacizumab, by independent review. Treatment-emergent adverse events leading to death (2.4% vs 1.5%), serious adverse events (17.6% vs 16.7%), and antidrug antibodies (6.5% vs 4.8%), were comparable in the MYL-1402O vs bevacizumab arms, respectively. The incidence of neutralizing antibody post-baseline was lower with MYL-1402O (0.6%) than with bevacizumab (2.5%). These findings confirm therapeutic equivalence of MYL-1402O to bevacizumab, providing opportunities for improving access to bevacizumab.